2016
DOI: 10.1111/ijcp.12798
|View full text |Cite
|
Sign up to set email alerts
|

Toileting behaviour and related health beliefs among Chinese female nurses

Abstract: Many female nurses engaged in unhealthy toileting behaviours and might not know what types of toileting behaviours are healthy. Nurses play an important role in patient education and are a major source of health information for society. It is particularly important to look more closely at toileting behaviour among nurses and implement education and training to promote healthy toileting behaviour and, in turn, optimise bladder health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 31 publications
2
56
1
1
Order By: Relevance
“…Our findings support those of previous studies that showed nurses had unhealthy toileting behaviours in terms of voiding their bladders (Liao et al., ; Xu et al., ). The most common behaviour was delayed voiding; more than 61% of nurses delayed emptying their bladders when busy, nearly half waited for extended periods of time (more than 4 hr) to urinate at work and nearly one‐third waited until they were unable to hold.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings support those of previous studies that showed nurses had unhealthy toileting behaviours in terms of voiding their bladders (Liao et al., ; Xu et al., ). The most common behaviour was delayed voiding; more than 61% of nurses delayed emptying their bladders when busy, nearly half waited for extended periods of time (more than 4 hr) to urinate at work and nearly one‐third waited until they were unable to hold.…”
Section: Discussionsupporting
confidence: 92%
“…OAB is more common among bedside nursing staff than in the general population. Due to busy work, nurses will adopt a series of unhealthy urination behaviours (Xu et al., ). Toileting behaviour is a comprehensive concept that includes voiding place, position, time, and style (Wang & Palmer, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, suppressing the urge to void may have no detrimental effect in the short term; however, long-term suppression may threaten bladder’s health [14]. Avoiding using public toilets or toilets at someone else’s house may lead to premature or delayed voiding [36]. Thus, educating patients to adopt healthy toileting behaviors to improve and maintain their optimal bladder health is essential.…”
Section: Discussionmentioning
confidence: 99%